PREVENTIONOF MYOCARDIAL INFARCTION WITH MODERN DIAGNOSIS AND DEVELOPMENT - Abduvaliyeva Feruza Mukhammatnurovna; Ibrohimov Muhammad Temurbek (Western European Studies, 2025)
This article provides detailed information about myocardial infarction, its causes, clinical signs, and treatment methods. Myocardial infarction commonly occurs in individuals suffering from chronic heart diseases and the accumulation of cholesterol in blood vessels over the years. The article discusses early diagnosis, therapeutic measures, and prevention strategies for myocardial infarction. It is beneficial for cardiologists, medical professionals, and individuals concerned about their health
Keywords: myocardial infarction; prevention; heart